Profitabilitas, Solvabilitas, Likuiditas, dan Nilai Perusahaan Rumah Sakit yang Terdaftar di BEI 2015-2019 - Umar, Anry; Tjong, William (E-Jurnal Akuntansi, 2021)
The hospital is a socio-economic service company. The research objective is to analyze the effect of profitability, solvency, and liquidity on the company value of the hospital industry. The study population was hospitals in sector 9 – trade, subsector 96 - health in the IDX for the 2015-2019. The sample was taken using nonprobability sampling method with purposive sampling technique of four issuers. This study uses a quantitative approach with data collection then processed with Eviews and the analysis technique used is panel data regression. From the results of the study using data panel regression with FEM approach and a significance value of 0.05; The p-value of ROE 0.3403, DER 0.0000 CR 0.0076. ROE, DER and CR have positive regression coefficients. The MIKA intercept value is 3.37330659, SAME -3.1121377, SILO 0.694458, and SRAJ -1.303740. R 2 of ROE, DER and CR on PBV is 76.9%. The conclusion in this study, DER and CR have a significant and positive effect on PBV. Meanwhile, ROE has no significant effect on PBV, but has a positive relationship. Keywords: The value of the company; Profitability; Solvency; Liquidity; Hospital.